STUDENTS’ RESPONSES TOWARDS TEACHER’S IMPLEMENTATION OF TPACK IN SENIOR HIGH SCHOOL AFTER PANDEMIC - Taufik, Beatrice Ellen; Sudarsono; Ikhsanudin; Rezeki, Yanti Sri (Prodi Administrasi Pendidikan Program Pascasarjana Universitas Riau, 2023)
Technological Pedagogical and Content Knowledge TPACK) is the knowledge that should be mastered by the teacher nowadays. The primary objective of this research is to investigate students' perceptions and reactions regarding the integration of Technological Pedagogical and Content Knowledge (TPACK) in a Senior High School setting. The study specifically targets twelfth-grade students enrolled in the Science Class at a selected Senior High School in Pontianak. The participants consist of a cohort of XII-grade students who provided their feedback by responding to a set of 35 statements pertaining to the teacher's utilization of TPACK. The collected data were subjected to analysis using SPSS Statistics 16.0. The findings reveal that the mean score for the teacher's TPACK is 3.57, with scores for Pedagogical Content Knowledge (PCK) at 3.75, instructional objectives content at 3.66, instructional representations and strategies at 3.62, and knowledge of students' understanding at 3.50. Additionally, nearly 100% of the students expressed strong agreement with statements highlighting the teacher's proficient pedagogical knowledge in implementing TPACK within the classroom. Consequently, the data analysis demonstrates a positive response towards the implementation of TPACK, indicating the successful integration of each element of TPACK among the XII Grade MIPA students.